Is attending birth dying out?: Trends in obstetric care provision among primary care physicians in British Columbia - Hedden, Lindsay (Can Fam Physician, 2019)
OBJECTIVE: To examine trends in and sociodemographic predictors of the provision of obstetric care within the primary care context among physicians in British Columbia (BC). DESIGN: Population-based, longitudinal cohort study using administrative data. SETTING: British Columbia. PARTICIPANTS: All primary care physicians practising in BC between 2005–2006 and 2011–2012. MAIN OUTCOME MEASURES: Fee-for-service payment records were used to identify the provision of prenatal and postnatal care and deliveries. The proportions of physicians who attended deliveries and who included any obstetric care provision in their practices were examined over time using longitudinal mixed-effects log-linear models. RESULTS: The proportion of physicians attending deliveries or providing any obstetric care declined significantly over the study period (deliveries: odds ratio [OR] of 0.92, 95% CI 0.89–0.95; obstetric care: OR = 0.92, 95% CI 0.89–0.95), and obstetric care provision accounted for a smaller proportion of overall practice activity (OR = 0.96, 95% CI 0.94–0.99). Female physicians had higher odds of including obstetric care in their practices (OR = 1.46, 95% CI 1.27–1.69), and by 2011–2012 had significantly higher odds of attending deliveries (OR = 1.22, 95% CI 1.05–1.38). Older physicians and those located in metropolitan centres were less likely to provide obstetric care or attend deliveries. CONCLUSION: The provision of obstetric care by primary care physicians in BC declined over this period, suggesting the possibility of a growing access issue, particularly in rural and remote communities where family physicians are often the sole providers of obstetric services.